Seasonal Abundance and Infestation of Fruit Fly on Cucumber (SAARC Journal of Agriculture, 2021)
Population dynamics and infestation of fruit fly, Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) was monitored on cucumber, Cucumis sativus using methyl eugenol trap during summer and autumn in 2017 at Gazipur, Bangladesh. Relationship between the abundance of fruit fly and meteorological factors was also studied. The fruit fly showed significantly higher abundance in summer compared to autumn. The larval population per fruit was found higher in summer (24.9 fruit-1) than that in autumn (1.5 fruit-1). The daily mean temperature had significant positive, light intensity had insignificant positive, relative humidity had insignificant negative and rainfall had insignificant negative correlation with fruit fly abundance. The temperature, light intensity, relative humidity and rainfall individually contributed to fruit fly abundance of 14.1 %, 24.0 %, 0.8 % and 1.8 %, respectively. The combined effect of the weather parameters on fruit fly abundance was 40.7 % and the equations were insignificant. The fruit fly showed significantly lower level of infestation in methyl eugenol treated plots as compared to controls in both summer and autumn.SAARC J. Agri., 18(2): 233-241 (2020)